Secondary structures of hexa-L-alanine host peptides substituted with L-leucine and L-isoleucine - Burke, J P W G (My University, 1991)
[Abbreviated Abstract. Open document to view full version]
A dissertation submitted in fulfillment of the requirements for the degree of l'laster of Science a:t the University of the witw'atersrand Johannesburg, January 1991